Spiritual leadership in forming organizational identity - Wulandari, Wulandari; Sampurna, Dian Surya (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2025)
This research explores the role and implementation of spiritual leadership in shaping the organizational identity of SMP DT Boarding School in Batam. The goal is to gain a comprehensive understanding of the school's culture and identity. The study employs a qualitative research method with a case study approach, featuring two respondents: the Headmaster and the Director of Finance and HR. Data collection techniques include interviews guided by general questions and a review of relevant literature. The findings indicate that DT School possesses a strong and well-defined organizational identity, and spiritual leadership is crucial for shaping and maintaining this identity. The focus is on character development, spiritual values, and fostering supportive relationships among members. Key factors that enhance the school's image and distinctive characteristics include its unique identity, a holistic approach to education, the founder's influence, and an organizational culture that reflects high values. These elements underscore DT School's commitment to spiritual values and character development. Public interest statements This study advocates for a transformative approach to education that prioritizes the development of both the mind and the spirit, benefiting individual students and the broader community.